Louis F. Post papers - Post, Louis F. (Louis Freeland), 1849-1928.; Post, Alice Thacher, 1853-1947.; Post, Louis F. (Louis Freeland), 1849-1928.; Post, Louis F. (Louis Freeland), 1849-1928.
Correspondence, diary, writings, articles, biographical material, scrapbooks, printed matter, and other papers relating to Post's career as an author, journalist, and public official. Documents his support of Henry George and the single tax, Swedenborgian (New Jerusalem Church) religious beliefs, policies favoring the civil rights of radicals, and views on society and progress. Documents the attempted impeachment of Post as U.S. assistant secretary of labor because of his policies relating to the deportation of political dissidents and radicals. Subjects also include an alleged buried treasure in South Africa and Ku Klux Klan trials in South Carolina. Includes manuscripts of Post's books, The Deportations Delirium of Nineteen-Twenty : A Personal Narrative of an Historic Official Experience (1923) and The Prophet of San Francisco : Personal Memories & Interpretations of Henry George (1930), and of his unpublished autobiography, Living a Long Life Over Again. Also includes papers of Post's wife, Alice Thacher Post. Correspondents include William Jennings Bryan and the Hackettstown Gazette.
Microfilm edition of Living a Long Life Over Again (container 4) available
Microfilm produced from originals in the Manuscript Division.
Journalist, lawyer, and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bryan, William Jennings, -- 1860-1925 -- Correspondence; George, Henry, -- 1839-1897.; United States. -- Department of Labor; Ku Klux Klan (19th cent.) -- Trials, litigation, etc; Hackettstown gazette; Buried treasure; Civil rights -- South Carolina; Civil rights -- United States; Deportation -- United States; Dissenters -- United States; Journalism -- United States; New Jerusalem Church; Progress; Radicals -- United States; Radicalism -- United States; Reconstruction (U.S. history, 1865-1877) -- South Carolina .; Single tax; Social change; Social history; Treasure troves -- South Africa; United States -- Politics and government -- 1865-1933.; United States -- Social conditions; Journalists; Lawyers; Public officials